2014
DOI: 10.1111/1462-2920.12513
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐scale metabolic reconstruction and constraint‐based modelling of the Antarctic bacterium Pseudoalteromonas haloplanktisTAC125

Abstract: The Antarctic strain Pseudoalteromonas haloplanktis TAC125 is one of the model organisms of cold-adapted bacteria and is currently exploited as a new alternative expression host for numerous biotechnological applications. Here, we investigated several metabolic features of this strain through in silico modelling and functional integration of -omics data. A genome-scale metabolic model of P. haloplanktis TAC125 was reconstructed, encompassing information on 721 genes, 1133 metabolites and 1322 reactions. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 83 publications
7
50
0
Order By: Relevance
“…This prompted a comprehensive characterization of this strains, through the analysis of its complete genome [7], its proteome in different conditions [14, 15], detailed growth phenotypes in complex media [9, 11]. The integration of genomic and expression data together with detailed physiological data allowed for the formulation of a genome scale metabolic model [16], that can be used to predict phenotypes and design experiments aimed at the optimization of Ph TAC125 metabolic capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This prompted a comprehensive characterization of this strains, through the analysis of its complete genome [7], its proteome in different conditions [14, 15], detailed growth phenotypes in complex media [9, 11]. The integration of genomic and expression data together with detailed physiological data allowed for the formulation of a genome scale metabolic model [16], that can be used to predict phenotypes and design experiments aimed at the optimization of Ph TAC125 metabolic capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reconstructed a genome-scale metabolic model of Ph TAC125, using it for inferring the metabolic adjustments of this bacterium induced by changes in gene expression following a temperature downgrade in this bacterium [17]. Here we used this model to investigate the metabolic rearrangements occurring during growth in a nutritionally rich medium.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic model used in this manuscript has been described in Fondi et al [17] and can be found in Additional file 1, together with the codes used to produce the results reported herein. The physiological data of Ph TAC125 growth in soy-peptone complex medium [14] was used to identify time steps corresponding to amino acid depletions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations